Para início de conversa - Almeida, Ricardo Santos de; Cerqueira, Sara Jane Lino de; Martins, Gleica Maria Correia; Neves, Jhonatan David Santos das (Revista Interseção, 2024)
Revista Interseção, Palmeira dos Índios/AL, v. 6., n. 1, nov. 2024, p. 1-5.